Modernização capitalista e decadência: o problema de consciência nos narradores de Angústia e o Amanuense Belmiro - Wagner Fredmar Guimarães Júnior (2016)
This work aims at developing a comparative study on the novels Angústia (1936), by Graciliano Ramos, and O amanuense Belmiro (1937), by Cyro dos Anjos, from a materialist perspective which considers the dialectical relationship between the subjectivity and the objectivity on the constitution of Luis da Silva and Belmiro Borbas consciousnesses. First, I try to understand the dialectical concept of the literary form in some authors of marxist tradition in Europe and in Brazil. On a second moment, I investigate the historical period represented by the novels (the last years of the XIX and first decades of the XX century in Brazil) in order to understand the origins of the social form that motivated these narratives and the context that motivated the Brazilian novel of the 1930s as a whole. Finally, I actually analyze the novels in order to discuss the insertion of the narrator-characters Luís and Belmiro in the modern world cities of Belo Horizonte and Maceió and how they face this new way of life and live the conflicts between past and present, tradition and modernity.